Concomitant loss of NDH complex‐related genes within chloroplast and nuclear genomes in some orchids. (11th April 2017) - Lin, Choun‐Sea; Chen, Jeremy J. W.; Chiu, Chi‐Chou; Hsiao, Han C. W.; Yang, Chen‐Jui; Jin, Xiao‐Hua; Leebens‐Mack, James; de Pamphilis, Claude W.; Huang, Yao‐Ting; Yang, Ling‐Hung; Chang, Wan‐Jung; Kui, Ling; et al.
Summary: The chloroplast NAD(P)H dehydrogenase‐like (NDH) complex consists of about 30 subunits from both the nuclear and chloroplast genomes and is ubiquitous across most land plants. In some orchids, such as Phalaenopsis equestris, Dendrobium officinale and Dendrobium catenatum, most of the 11 chloroplast genome‐encoded ndh genes (cp‐ ndh ) have been lost. Here we investigated whether functional cp‐ ndh genes have been completely lost in these orchids or whether they have been transferred and retained in the nuclear genome. Further, we assessed whether both cp‐ ndh genes and nucleus‐encoded NDH‐related genes can be lost, resulting in the absence of the NDH complex. Comparative analyses of the genome of Apostasia odorata, an orchid species with a complete complement of cp‐ ndh genes which represents the sister lineage to all other orchids, and three published orchid genome sequences for P. equestris, D. officinale and D. catenatum, which are all missing cp‐ ndh genes, indicated that copies of cp‐ ndh genes are not present in any of these four nuclear genomes. This observation suggests that the NDH complex is not necessary for some plants. Comparative genomic/transcriptomic analyses of currently available plastid genome sequences and nuclear transcriptome data showed that 47 out of 660 photoautotrophic plants and all the heterotrophic plants are missing plastid‐encoded cp‐ ndh genes and exhibit no evidence for maintenance of a functional NDH complex. Our data indicate that the NDH complex can be lost in photoautotrophic plant species. Further, the loss of the NDH complex may increase the probability of transition from a photoautotrophic to a heterotrophic life history. Significance statement: The NDH complex is composed of multiple genes encoded by the chloroplast and nuclear genomes. Some photoautotrophs have been shown to lack all the chloroplast genome‐encoded ndh genes but the genes in the nucleus have never been assessed. Through sequencing the ndh ‐complete orchid genome, Apostasia odorata, we showed that the missing ndh genes in ndh ‐free orchids are not transferred to the nucleus, and the nuclear NDH‐related genes were also lost resulting in no NDH complex.